Salud bucodental y su impacto en la calidad de vida en los niños menores de 5 años de edad, pertenecientes a la parroquia Manú cantón Saraguro provincia de Loja, durante el periodo septiembre 2021 - marzo 2022 - Calderón Chamba, Cristhian Iván (2022)
The quality of life associated with oral health refers to the impacto of oral health or disease on daily activities and the well-being of a person. Objetive: To diagnose parents´ perception of oral health and its impact on the quality of life of children under five years of age and their families belonging to the Manu parish, Saraguro cantón, Loja Province. Materials and methods: We evaluated a sample of 146 children under five years of age and their representatives; we administered this cross-sectional study on parents/guardians belonging to the Manu parish. We considered different variables for the study; and, as well as the oral health status of the study subjects at that time. The analytical criteria of the parents were employed to evaluate their perception concerning the oral health status of their children. We partitioned respondents according to the locality of residence, level of perception, age, and sex, among others. Initially, we socialized the project; and then the Ec-ECOHIS (Early Childhood Oral Health Impact Scale) survey was applied. With the data compiled, we administered a statistical analysis using Spss software. We performed Normality tests on the data collected, contingency, and CHI square. Results: 123 children representing 84.2% of the study sample showed a positive impact on the child´s quality of life, while 23 children representing 15.8% of the study sample showed a negative impact. On the other hand, 121 parents representing 82.9%, presented a positive impact on the family, while 25 parents representing 17.1%, presented a negative impact. Conclusion: Therefore, we deduced that despite the alterations in oral health that this specific age group may present, these do not compromise to a great extent or limit the quality of life of the infants and their families